2019
DOI: 10.1111/jon.12676
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐Based Manual versus Automated Corpus Callosum Volumetric Measurements in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE Corpus callosum atrophy is a neurodegenerative biomarker in multiple sclerosis (MS). Manual delineations are gold standard but subjective and labor intensive. Novel automated methods are promising but require validation. We aimed to compare the robustness of manual versus automatic corpus callosum segmentations based on FreeSurfer. METHODS Nine MS patients (6 females, age 38 ± 13 years, disease duration 7.3 ± 5.2 years) were scanned twice with repositioning using 3‐dimensional T1‐weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
(56 reference statements)
1
11
1
1
Order By: Relevance
“…The variable error thus introduced causes the correlation of CCA vs. CCV to suffer. FreeSurfer version 6.0 was however found to correlate well with manual measurement using the longitudinal stream by Platten et al (9). The correlation was worse using the cross-sectional stream as is the case in the present study.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…The variable error thus introduced causes the correlation of CCA vs. CCV to suffer. FreeSurfer version 6.0 was however found to correlate well with manual measurement using the longitudinal stream by Platten et al (9). The correlation was worse using the cross-sectional stream as is the case in the present study.…”
Section: Discussioncontrasting
confidence: 43%
“…Repeated measurements in the same slice using standard PACS area-tracing tools gave highly uniform results suggesting there is no advantage to multiple averaged measurements over single measurements. CCA measurements have been found to be highly repeatable regardless of operator experience (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies employing corpus callosum segmentations have reported varying levels of success. Manual segmentations have been shown useful and are often used as gold standard when comparing other methods 9,12 . However, manual measurements are tedious and have an inherent inter‐ and intrarater variability.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods for segmenting the corpus callosum based on MRI, including manual segmentations, 9 atlas‐based software, such as FreeSurfer, 10 and machine learning algorithms 11 . FreeSurfer can render 3D segmentations of the corpus callosum with high precision but lower accuracy, as compared to manual delineations 12 . In recent years, artificial intelligence has become more widely applied in radiology and convolutional neural networks, a subclass of deep learning inspired by human layered neuronal connectivity, are particularly useful in segmenting radiological images 13 .…”
Section: Introductionmentioning
confidence: 99%